An Exploratory Research on Participatory Planning Processes and the Interaction between Citizens, Public Administration, and Professionals - VOINEA Carmen-Giorgiana; PROFIROIU Constantin-Marius (Applied Research in Administrative Sciences)
Drawing on the data from an online survey and a focus group, the article explores the public participation of citizens with a focus on participatory planning processes. The exploratory research tackles participatory initiatives and interactions between citizens, public administration, and professionals that aim to improve the well-being of citizens in their cities of residence. The research employed a theoretical view of collaborative public participation, one that is not, however, confined to a dualistic approach, but one in which the citizens value the existence of intermediary actors or structures to guide public participation. Moreover, adversarial potential in participatory planning processes is not excluded, especially as participation involves a diverse network of actors. In the context of a significant consensus regarding the importance of citizen participation in all stages of decision making, the article shows that there is, however, a low level of information regarding participatory planning processes.